Catabolism of phenylacetic acid in Penicillium rubens. Proteome-wide analysis in response to the benzylpenicillin side chain precursor - Jami, Mohammad-Saeid; Martín, Juan-Francisco; Barreiro, Carlos; Domínguez-Santos, Rebeca; Vasco-Cárdenas, María-Fernanda; Pascual, María; García-Estrada, Carlos (Journal of proteomics, 2018)
Biosynthesis of benzylpenicillin in filamentous fungi (e.g. Penicillium chrysogenum - renamed as Penicillium rubens- and Aspergillus nidulans) depends on the addition of CoA-activated forms of phenylacetic acid to isopenicillin N. Phenylacetic acid is also detoxified by means of the homogentisate pathway, which begins with the hydroxylation of phenylacetic acid to 2-hydroxyphenylacetate in a reaction catalysed by the pahA-encoded phenylacetate hydroxylase. This catabolic step has been tested in three different penicillin-producing strains of P. rubens (P. notatum, P. chrysogenum NRRL 1951 and P. chrysogenum Wisconsin 54–1255) in the presence of sucrose and lactose as non-repressing carbon sources. P. chrysogenum Wisconsin 54–1255 was able to accumulate 2-hydroxyphenylacetate at late culture times. Analysis of the P. rubens genome showed the presence of several PahA homologs, but only Pc16g01770 was transcribed under penicillin production conditions. Gene knock-down experiments indicated that the protein encoded by Pc16g01770 seems to have residual activity in phenylacetic acid degradation, this catabolic activity having no effect on benzylpenicillin biosynthesis. Proteome-wide analysis of the Wisconsin 54–1255 strain in response to phenylacetic acid revealed that this molecule has a positive effect on some proteins directly related to the benzylpenicillin biosynthetic pathway, the synthesis of amino acid precursors and other important metabolic processes. The adaptive response of Penicillium rubens to benzylpenicillin production conditions remains to be fully elucidated. This article provides important information about the molecular mechanisms interconnected with phenylacetate (benzylpenicillin side chain precursor) utilization and penicillin biosynthesis, and will contribute to the understanding of the complex physiology and adaptation mechanisms triggered by P. rubens (P. chrysogenum Wisconsin 54–1255) under benzylpenicillin production conditions. [Display omitted] •Pc16g01770 seems to keep residual phenylacetate hydroxylase activity.•Enzymes related to penicillin biosynthesis are positively affected by phenylacetate.•Phenylacetate affects important metabolic processes (e.g. SAM synthase, GDH).